Considering patient perspectives in economic evaluations of health interventions - Fu, Rui; Ng, Vivian; Liu, Michael; Wells, David; Yurga, Emre; Nauenberg, Eric (Frontiers in Public Health, 2023)
Current guidelines for evaluating the cost-effectiveness of health interventions commonly recommend the use of a payer and/or a societal perspective. This raises the concern that the resulting reimbursement decision may overlook the full spectrum of impacts and equity considerations. In this paper, we argue that a potential solution is to supplement a societal-or payer-perspective economic evaluation with an additional evaluation accounting for exclusively the patient perspective. We present five categories of health interventions for which a patient-perspective analysis may be informative including those 1) that cross the definitional boundary between drugs and non-drug technologies; 2) affect patient adherence to protocol; 3) represent revolutionary treatments for genetic disorders; 4) with an incremental cost-effectiveness ratio involving slightly less effective, but substantially less costly, than the current standard; and 5) have been previously approved for funding but now being targeted for potential delisting or disinvestment. Real-world examples are discussed in detail. Lived experience individuals were invited to provide vignettes. Discussions are provided regarding how to incorporate patient inputs to improve patient-centered decision-making.